A Cultural Management Model for Building an Anti-Bullying Environment in Islamic Boarding Schools: A Case Study of Pondok Pesantren Darussalam Paciran Lamongan - Muhammad Nur Romdloni; Akhmad Khamdani; Lora Hilal Fikri; Akhmad Zaeni (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study examines how pesantren culture management can be developed as a strategic model to build an anti-bullying environment for santri, using Pondok Pesantren Darussalam Paciran, Lamongan, as the case. Bullying among santri is often rooted not merely in individual behavior but in the organizational culture of the boarding school, including seniority patterns, weak supervision, and unwritten norms that normalize harsh treatment among peers. This research employs a qualitative case study approach, with data collected through in-depth interviews with the kiai, pengasuh, and santri, participant observation of daily boarding life, and documentation of pesantren regulations. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that Pondok Pesantren Darussalam develops an anti-bullying culture through four interrelated components: internalization of Islamic values, exemplary leadership from the kiai, structured and participatory supervision, and an educative sanction system supported by a santri reporting mechanism. These components form an integrated cultural management model that shifts bullying prevention from reactive punishment toward proactive value-based culture building. The study concludes that deliberate pesantren culture management can significantly reduce bullying risk and strengthen a safe, brotherly, and educative santri environment.